2015
DOI: 10.1016/j.fsigss.2015.09.189
|View full text |Cite
|
Sign up to set email alerts
|

The potential use of fungi community in postmortem interval estimation in China

Abstract: Body provides a home for diverse commensal microbiota. Microorganisms such as fungi have major roles in this microbial community stability. Postputrefaction fungi have been recorded in association with decomposed mammalian cadavers in disparate regions. The succession and diversity of these fungi are reviewed with a view to their potential as a forensic tool. The researches of mycology would be an interface to forensic investigation and may provide a means to estimate PMI within serious decomposition. To evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 6 publications
3
9
3
Order By: Relevance
“…Abundance This result is in contrast with that of Metcalf et al [32], who suggested that Basidiomycota are particularly active during the active decay stage, but is in agreement with Fu et al [33], who noticed a decrease in the abundance of this phylum in the rectum of decomposing rats with increasing time after death. In our case, the carcasses reached the active stage of decomposition between one and two months, but Basidiomycota decreased rapidly with the introduction of the carcass in the soil (from control to P1), with Piskurozymaceae family being the most abundant one after one month, and with all the families, including Entolomataceae, Psathyrellaceae disappearing completely after two, fourand six-months post-mortem, suggesting their limited role during the active decomposition of the carcasses in this study.…”
Section: Librarysupporting
confidence: 82%
See 2 more Smart Citations
“…Abundance This result is in contrast with that of Metcalf et al [32], who suggested that Basidiomycota are particularly active during the active decay stage, but is in agreement with Fu et al [33], who noticed a decrease in the abundance of this phylum in the rectum of decomposing rats with increasing time after death. In our case, the carcasses reached the active stage of decomposition between one and two months, but Basidiomycota decreased rapidly with the introduction of the carcass in the soil (from control to P1), with Piskurozymaceae family being the most abundant one after one month, and with all the families, including Entolomataceae, Psathyrellaceae disappearing completely after two, fourand six-months post-mortem, suggesting their limited role during the active decomposition of the carcasses in this study.…”
Section: Librarysupporting
confidence: 82%
“…suggesting that the Mortierellomycota also may have a role during the early decomposition stages of the carcasses, although this could be minor compared with their activity during the advanced stages of decay. We did not find an increase in Zygomycota and in Chytridiomycota with time, as found in contrast by Fu et al [33] in the rectum of decomposing rats.…”
Section: Librarycontrasting
confidence: 76%
See 1 more Smart Citation
“…Phyllum Ascomycota was the most representative (179; 80.3%), followed by Zygomycota (33, 14.8%) and Basidiomycota (11; 4.9%) ( Table 2). In China 83 found Ascomycota the most dominant phyllum, followed by Basidiomycota, Zygomycota and Chrytridiomycota. (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…França, 4 report that among the most complex problems is the determination of the approximate time of death in the absence of chronological elements, such as those obtained from necrofauna, capable of providing a sequential characterization of cadaveric phenomena. In recent decades, studies describing the use of fungi as a forensic tool have been published referring to the countries: Japan, 80,81 United States, 82 China, 83 Germany, 84 Argentina, 70 Romania 85 and Brazil. 40,[86][87][88] In this study, 223 fungal specimens (Figure 3), distributed in three phylla, twelve orders, 21 genera and 35 species, were identified.…”
Section: Resultsmentioning
confidence: 99%